Cloning, expression and characterization of an A6-related protein - Rohwer, Andreas; Marks, Friedrich (EJB, 1999)
By interaction cloning (yeast two-hybrid system) using the catalytic domain of protein kinase Cζ (PKCζ) as bait, we cloned a human full-length cDNA with 62% nucleotide homology to the A6 protein recently cloned and characterized by Beeler et al. [Beeler, J.F., LaRochelle, W.J., Chedid, M., Tronick, S.R. & Aaronson, S. A. (1994) Mol. Cell. Biol.14, 982-988]. The deduced amino acid sequence (349 amino acids) of the A6-related protein (A6rp) contained potential actin-binding sites and ATP-binding sites. We also cloned the murine homolog of A6rp. Human A6rp was expressed in an in-vitro transcriptional/translational system with an apparent molecular mass of 40 kDa and as a glutathione S-transferase (GST) fusion protein in bacteria. A polyclonal anti-(A6rp) was raised in rabbits and used for the identification of A6rp by immunoblotting. A6rp was found to be expressed at the mRNA and the protein levels in all cells and tissues investigated. GST-A6rp was phosphorylated by PKCζ but not significantly by other PKC isoenzymes. Moreover, it was phosphorylated by casein kinase 2 and most effectively by the tyrosine kinase Src. In contrast to GST-A6rp, GST-A6 was also phosphorylated by PKC isoforms other than PKCζ and strongly by CK2, but just weakly by Src. In contrast to the results of Beeler et al. on β-galactosidase-A6, we were unable to demonstrate autokinase activity or tyrosine phosphorylation of either GST-A6 or GST-A6rp. In accordance with the potential ATP-binding sites, both proteins were able to bind ATP.
Elektronische Reproduktion der Druckausgabe
Gesehen am 22.04.2021